DEVELOPMENT OF GENERAL PHYSICS MODULE INTEGRATED OF QURANIC VERSES TO DEVELOP THE RELIGIOUS CHARACTER OF STUDENTS AT ADZKIA UNIVERSITY (Universitas PGRI Sumatera Barat, 2022)
Teaching materials in the form of general physics modules integrated with quran verses developed by lecturers can improve students' religious character. Type of research is development research with Four-D Model consisting of four main stages, namely: defining, designing, developing, and disseminating. The instruments used to collect data were expert validation sheets, module implementation observation sheets, student response questionnaires, and student character assessments. The results of this study showed that the developed module met the very valid criteria with a validity of 94. The average activity implementation was 1.57, which means that all activities were carried out properly. Response of student about the module is known that the average practicality of the module is 91, which means the module is very practical. student character has an average core of 79 in the good category. Thus, the general physics module has been developed were valid and practical.